Over-expression of mitochondrial creatine kinase in the murine heart improves functional recovery and protects against injury following ischaemia–reperfusion. Issue 6 (2nd March 2018) - Whittington, Hannah J; Ostrowski, Philip J; McAndrew, Debra J; Cao, Fang; Shaw, Andrew; Eykyn, Thomas R; Lake, Hannah A; Tyler, Jack; Schneider, Jurgen E; Neubauer, Stefan; Zervou, Sevasti; Lygate, Craig A
Abstract: Aims: Mitochondrial creatine kinase (MtCK) couples ATP production via oxidative phosphorylation to phosphocreatine in the cytosol, which acts as a mobile energy store available for regeneration of ATP at times of high demand. We hypothesized that elevating MtCK would be beneficial in ischaemia–reperfusion (I/R) injury. Methods and results: Mice were created over-expressing the sarcomeric MtCK gene with αMHC promoter at the Rosa26 locus (MtCK-OE) and compared with wild-type (WT) littermates. MtCK activity was 27% higher than WT, with no change in other CK isoenzymes or creatine levels. Electron microscopy confirmed normal mitochondrial cell density and mitochondrial localization of transgenic protein. Respiration in isolated mitochondria was unaltered and metabolomic analysis by 1 H-NMR suggests that cellular metabolism was not grossly affected by transgene expression. There were no significant differences in cardiac structure or function under baseline conditions by cine-MRI or LV haemodynamics. In Langendorff-perfused hearts subjected to 20 min ischaemia and 30 min reperfusion, MtCK-OE exhibited less ischaemic contracture, and improved functional recovery (Rate pressure product 58% above WT; P < 0.001). These hearts had reduced myocardial infarct size, which was confirmed in vivo : 55 ± 4% in WT vs. 29 ± 4% in MtCK-OE; P < 0.0001). Isolated cardiomyocytes from MtCK-OE hearts exhibited delayed opening of the mitochondrial permeability transition pore (mPTP) compared to WT, which was confirmed by reduced mitochondrial swelling in response to calcium. There was no detectable change in the structural integrity of the mitochondrial membrane. Conclusions: Modest elevation of MtCK activity in the heart does not adversely affect cellular metabolism, mitochondrial or in vivo cardiac function, but modifies mPTP opening to protect against I/R injury and improve functional recovery. Our findings support MtCK as a prime therapeutic target in myocardial ischaemia.